PENGARUH PROFITABILITAS, LEVERAGE, DAN CAPITAL INTENSITY TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN PERTAMBANGAN - Sari, Sonia Nanda; Widyastuti, Tri (Investama : Jurnal Ekonomi dan Bisnis, 2025)
The decline in tax contributions from the mining sector indicates the potential for tax avoidance by companies in the sector. Tax avoidance is a concern because it can significantly affect state revenues. This study aims to examine the effect of profitability (Net Profit Margin), leverage (Debt to Equity), and capital intensity (Capital Intensity Ratio) on tax avoidance (Cash Effective Tax Rate) in mining companies listed on the Indonesia Stock Exchange in 2022-2024. This research is a type of quantitative research. The data used is secondary data obtained from financial reports on the official website of the Indonesia Stock Exchange. Data analysis was conducted using multiple linear regression to test the effect of each variable on tax avoidance, with data processing using the SPSS 27 program. The results of the study showed that profitability partially affected tax avoidance, while leverage and capital intensity did not affect tax avoidance. Profitability, leverage, and capital intensity simultaneously affected tax avoidance.